2006
DOI: 10.1111/j.1469-7580.2006.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

The superior colliculus of the camel: a neuronal‐specific nuclear protein (NeuN) and neuropeptide study

Abstract: In this study we examined the superior colliculus of the midbrain of the one-humped (dromedary) camel, Camelus dromedarius , using Nissl staining and anti-neuronal-specific nuclear protein (NeuN) immunohistochemistry for total neuronal population as well as for the enkephalins, somatostatin (SOM) and substance P (SP). It was found that, unlike in most mammals, the superior colliculus is much larger than the inferior colliculus. The superior colliculus is concerned with visual reflexes and the co-ordination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Although we did not do so here, MS methods can in principle also be used to study peptide distribution across cortical layers. Also consistent with our results are previous reports of Enkephalines in the superior colliculus [58]. While Enkephalins have been mostly associated with addiction and pain, our studies suggest that they may also play an important role in maintaining the function of the visual system.…”
Section: Discussionsupporting
confidence: 82%
“…Although we did not do so here, MS methods can in principle also be used to study peptide distribution across cortical layers. Also consistent with our results are previous reports of Enkephalines in the superior colliculus [58]. While Enkephalins have been mostly associated with addiction and pain, our studies suggest that they may also play an important role in maintaining the function of the visual system.…”
Section: Discussionsupporting
confidence: 82%
“…Conversely, Telford et al (1996) reported that the stratum griseum of Sprague-Dawley rats is further divided into stratum griseum superficiale, stratum opticum, stratum griseum intermediale, stratum album intermediale and stratum griseum profundum, suggesting a good eyesight. Similarly, Mensah-Brown and Garey (2006) recorded six laminae in the rostral colliculus of camels. They also concluded that visual system of the camel is well developed suggesting a good eyesight in the camel.…”
Section: Discussionmentioning
confidence: 97%
“…It is composed of a pair of rostral and a pair of caudal colliculi. The rostral colliculus is the visual reflex centre, concerned with the co-ordination of reflexive movements of the head, neck and eyes, as well as focusing of the lens and visual tracking of objects (Mensah-Brown and Garey, 2006;Walton et al, 2007). The caudal colliculus is the acoustic reflex centre.…”
Section: Introductionmentioning
confidence: 99%
“…1992; Stamatakis et al. 2004; Mensah‐Brown and Garey 2006). NeuN immunoreactivity has also been described in human primary brain tumors and neuronal‐cell lines (Mullen et al.…”
mentioning
confidence: 99%